Patriarchy after patriarchy gender relations in Turkey and in the Balkans, 1500 - 2000 - Kaser, Karl 1954-2022 (Wien Berlin Münster Lit, 2008)
"Since the second half of the 1980s social movements, which questioned the legitimacy of the hitherto seemingly stable systems of Kemalist Turkey and socialist Balkans, won ground. Political Islam shuck Turkey; in the Balkan socialist countries the dams broke, and parliamentary democracies replaced monolithic socialist regimes. These processes have not been gender neutral. Therefore the central question is - after the abolition of patriarchy and the official installation of gender equality - are patriarchy and female discrimination returning in the region through the backdoor, although in a modernized version?"--BOOK JACKET
Literaturverz. S. 283 - 314
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Sex role -- Balkan Peninsula; Sex role -- Turkey; Balkan Peninsula -- Social conditions; Turkey -- Social conditions